(untitled) (Scientific journal of the Fergana State University, 2023)
Parameters of antiferromagnetic exchange values between paramagnetic ions based on the analysis of electron paramagnetic resonance spectra of heterobimetallic oxo-carboxylates with the general formula of [Fe3+2M2+O(RCOO)6(H2O)3]·nH2O (M=Mn, Ni, Co, Cu) measured in the temperature range 4.2-300 K according to the Heisenberg-Dirac-van-Fleck model evaluated and showed that the compounds have an μ3-oxocluster structure